(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the advantages of using information technology and multimedia tools in teaching French, as well as the importance of multimedia resources and technology in the process of teaching French.